Manual de funcionamiento, mantenimiento y aplicación pedagógica de los equipos ph metro portátil con cuchilla para carne ape-ph8500-mt y ph metro para productos semi sólidos ph60s para el Laboratorio de investigación en cárnicos de la Carrera de Agroindustria de la Universidad Técnica de Cotopaxi. - Pastuña Pastuña, Aida Verónica (2022)
This integrative project aims to develop an operation and maintenance manual. It will be used for portable potentiometers, for the PH8500-MT meat, and PH60S semi-solid products in the meat research laboratory of the Agroindustry program at the Technical University of Cotopaxi. It was elaborated employing qualitative methodology, using bibliographic, descriptive, and applied research. Likewise, the techniques and instruments used were observation, the file, and the guide sheet, which aided in collecting information on the object of the project and the solution to the problem posed. Thus, the operation and maintenance manual (routine, preventive, predictive, and corrective) was developed, detailing the equipment’s generalities, requirements, parts, and mode of operation to prolong its useful life. Thus, the manual guides teachers, technical personnel, and students to use of the portable potentiometers for meat PH8500-MT and semi-solid products PH60S in subsequent practices. Students of the Agroindustry career can relate theoretical with practical knowledge. In addition, a practical demonstration was carried out to show the correct operation, and the potentiometers were calibrated by taking the pH of the different raw materials for the production for Frankfurter-type sausage, chicken sausage, as well as the final products produced, where the results obtained were compared bibliographically with the INEN 78; 2015 standards with the pedagogical application of the equipment within the meat research laboratory.